Agroecosystem’s contributions to people: how ranchers and specialists perceive threatened Espinal forests used for cattle-grazing - Rojido, Ignacio Jose; Anderson, Christopher B.; Tagliaferro, Marina Beatriz; Canavelli, Sonia Beatriz (Springer, 2024)
Scientists and managers seek to implement more inclusive and effective conservation strategies by incorporating plural valuations of nature and nature’s contributions to people (NCP) into research and decision-making. For Argentina’s threatened Espinal ecoregion, this need is particularly acute. In Entre Ríos province, practically all of these forests are devoted to production, and the expanding agricultural frontier increases their conversion to crops. We surveyed family ranchers and agricultural/environmental specialists, two key stakeholders for managing Espinal forests used for cattle grazing. Employing a sociocultural valuation, we determined i) stakeholder recognition of the Espinal’s NCP and its support for quality of life, ii) similarity between stakeholder valuations (importance: 0 = none; 4 = very) of NCP and dimensions of well-being derived from the Espinal, and iii) relationship between ecological (e.g., forest degradation) and social (e.g., place of residence) factors and perceptions of the forest. Ranchers recognized more NCP and quality-of-life aspects, and the importance to their well-being tended to be greater than specialists. Both groups valued regulating and non-material NCP above material contributions and considered that forests are very important for physical and mental health. Finally, only rancher perceptions varied with tested variables, depending on degradation levels of forests with which they have the most contact and/or carry out their activities, the number of uses and recreational activities they carry out in forests, their knowledge of forests, and their place of residence. This study illustrates common ground upon which to promote synergies between production and conservation in Espinal-cattle agroecosystems.